Harmonisation of accounting information system in a new environment for a Malaysian agricultural company / Kamaruzzaman Muhammad - Muhammad, Kamaruzzaman (2018)
Organisational change may arise when an organisation has undergone a transformation in its structure and activities with the ultimate goal of increasing its organisational performance. Understandably, each organisation that has experienced organisational change would face a different form of change and employ different ways of solving issues surrounding the change. Although studies in the organisational change literature have provided some evidences, there are limited evidences that relate to Accounting Information System (AIS) change and new government policy. Therefore, this study aims at providing better understanding on the forces, nature and process of the AIS change in a Malaysian agricultural company. To achieve this aim, this study develops a research framework that utilises two research frameworks developed by Dillard, Rigsby and Goodman (2004) and Burns and Scapens (2000). A case study approach using triangulation method of interview and content analysis were employed in this study. Findings of this study shows the existence of external forces of AIS change comprising of New Economic Model, Economic Transformation Program, Regulators and Listing Consultants in influencing the changes to the company's status (from a private company into a public listed company), business model and corporate structure which in turn became the internal forces of AIS change. This study also shows that upon listing, the existing system was upgraded, and five new systems were employed. The change to the AIS structure is necessary to accommodate the expectation of the company's new business model and corporate structure. The new AIS structure is required to support the strategic goals in increasing the company's performance in terms of business expansion, efficiency and business communication. The nature of AIS change varies. Findings show some modifications to the existing system and acquisition of new systems comprising of evolutionary change and revolutionary change. In terms of progressive change or regressive change, the acquisition process of all systems went through progressive change. In terms of formal change or informal change, all systems went through formal change process. The findings of this study implicate that the company has undergone AIS change upon listing which were influenced by the external and internal forces and thus, support the findings in the organisational change literature. Finally, this study shows that the company has employed several strategies in ensuring successful AIS change. The findings of this study serve as a guideline for business practices and contribute to the academic knowledge and literature.